Design with the sun passive solar architecture - Balibrera, Mario; Evans, Dana.; Danamar Film Productions (Oley, Pa. Bullfrog Films, 1979)
Focus on Sonoma County, Calif., as a haven for innovatively designed passive solar houses in which architects and engineers have worked together to maximize the relationship between the sun and the earth at various seasons of the year through such features as direct gain, trombe wall, and solar greenhouse structures. Architects, designers, contractors, and residents note this regional approach as they describe various houses.
Cinematography, Mario Balibrera, Clint Dougherty ; graphics, W. G. Johnson, New Mexico Solar Energy Association, SEA group ; editor, Mario Balibrera.
DVD
Keywords: Solar houses -- California -- Sonoma County -- Design and Construction; Solar energy -- California -- Sonoma County -- Passive systems; Video discs